A Distribution in Motion: The Case of Argentina - Guillermo Cruces; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2008)
This paper documents the changes in the income distribution in Argentina from the mid-1970s to the mid-2000s. Over the period inequality increased substantially. Two types of episodes have shaped this upward trend: deep macroeconomic crises and periods of sudden and intense economic liberalization. The sizeable rise in inequality in the 1990s seems to be associated to reallocations against unskilled-labor intensive sectors, and skilled-biased technological change within most sectors, both factors stimulated by the process of economic integration. The depth and speed of the reforms and the scarcity of public policies to ease the transition contributed to the particular severity of the income distribution changes. The macro crises and the subsequent recoveries contributed to the volatility of inequality along this upward trend. The large macroeconomic crisis of 2001/02 triggered a large jump in inequality, although income disparities returned to pre-crisis levels as the economy recovered fast, and large cash transfer programs were implemented.
Keywords: C15; D31; I21; J23; J31; 330; inequality; distribution; integration; wages; Argentina; Einkommensverteilung; Argentinien